Validity of Dyscalculia Module for Pupils with Dyscalculia - Soo May, Yoong (Department of Special Education, 2024)
There are three types of specific learning disorders, namely dyscalculia, dyslexia, and dysgraphia. Pupils with dyscalculia facing difficulties in acquiring basic arithmetic skills. Dyscalculia Module has been designed and developed for pupils with dyscalculia to learn basic arithmetic skills. The purpose of this study is to measure the validity of Dyscalculia Module among pupils with dyscalculia in basic arithmetic skills. Expert validation was carried out to measure the face validity, content validity, and activities suitability of Dyscalculia Module. Three experts in language were invited to evaluate the face validity, whereas nine experts in the field of special education, learning difficulties, Mathematics education, and module development were invited to evaluate the content validity and activities suitability. Percentages of validity achievement was used to measure the face validity, content validity, and activities suitability. The result shows that the language and terminology used in Dyscalculia Module achieved a good face validity measurement, with a face validity percentage of 86.66%. Dyscalculia Module has also achieved a good content validity measurement, with a content validity percentage of 87.50%. Other than that, the activities in Dyscalculia Module achieved a good suitability measurement, with activities suitability percentage of 85.44%. In conclusion, Dyscalculia Module achieved acceptable face validity, content validity, and suitability of activities. This study implicated that Dyscalculia Module is valid and the activities designed are suitable to improve the basic arithmetic skills among pupils with dyscalculia in primary schools. Future studies are recommended to implement Dyscalculia Module to pupils with dyscalculia in Malaysia and other countries.